Candida tropicalis able to produce yeast single cell protein using sugarcane bagasse hemicellulosic hydrolysate as carbon source. Issue 1 (January 2018) - Magalhães, Cristina Emanuela Barbosa; Souza-Neto, Manoel Santiago; Astolfi-Filho, Spartaco; Matos, Italo Thiago Silveira Rocha
Abstract: The world demand for foods will be the most important bottle-neck for human being maintenance. In this context, the research for alternative proteins sources aiming human and animal feeding is a necessary approach. A wild-type strain of Candida tropicalis (KP276650) was identified as potential yeast single cell protein (YSCP) producer using sugarcane bagasse hemicellulosic hydrolysate (SBHH) as substrate. Were evaluated the cell growth and sugar consumption along fermentation assay. Biomass yield (YB, g g −1 ), protein percentage (%), protein yield (YP, g g −1 ) and yeast biomass productivity (YBP, g L −1 h −1 ) were calculated. Fermentation assay reach a total of 96 h, being the total reducing sugar present in the media (59.94 g L −1 ) fully consumed. Final biomass produced was 16.97 g L −1, and the YBP was 0.1767 g L −1 h −1 . Percentage of protein in yeast biomass produced was 60.05%, biomass yield (YB ) and protein yield (YP ) were, respectively, 0.28 and 0.17 g g −1 . The YB and YP obtained are close to the observed for some industrial strains of yeasts. The percentage of protein is greater than the expected for most of yeasts and fungi. These results indicate that the using of C. tropicalis (KP276650) for YSCP production may to aggregate high value for sugarcane bagasse.